2022
DOI: 10.3389/fpsyg.2021.784173
|View full text |Cite
|
Sign up to set email alerts
|

Reviewers’ Identity Cues in Online Product Reviews and Consumers’ Purchase Intention

Abstract: This research performs three experiments to investigate the influence mechanisms of identity cues in product reviews on consumers’ purchase intention, and to examine the effects of reference groups. The results indicate that: (1) identity cues in positive reviews have a significant positive impact on consumers’ purchase intention, while identity cues in negative reviews have a significant negative impact on consumers’ purchase intention; in addition, identity cues play a greater role in amplifying the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
4
0
2
Order By: Relevance
“…In this study, social support refers to the help consumers receive from interpersonal relationships (e.g., family and friends) or other groups (J. Li & Liang, 2022; Zimet et al, 1988). Available literature proves that social support significantly affects consumer behavior (e.g., Bacharach et al, 2010; Xu et al, 2015; Yahia et al, 2018; D. H. Zhu et al, 2016).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, social support refers to the help consumers receive from interpersonal relationships (e.g., family and friends) or other groups (J. Li & Liang, 2022; Zimet et al, 1988). Available literature proves that social support significantly affects consumer behavior (e.g., Bacharach et al, 2010; Xu et al, 2015; Yahia et al, 2018; D. H. Zhu et al, 2016).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Available literature proves that social support significantly affects consumer behavior (e.g., Bacharach et al, 2010; Xu et al, 2015; Yahia et al, 2018; D. H. Zhu et al, 2016). For instance, social support positively affects consumer trust (Yahia et al, 2018), consumer satisfaction (D. H. Zhu et al, 2016), and purchase intention (J. Li & Liang, 2022). Besides, social support is considered one of the influencing factors of green consumption (see Nair & Little, 2016 for a review).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, the information of the reviewers (reviewer's identity cues) comes to the consumers' aid. Previous studies have found that reviewers' identity cues significantly correlate to consumers' purchase intentions based on the polarity of the review (Li and Liang, 2021). Additionally when the reviewers are experts or disclose their identity, their reviews are more likely to be helpful (Filieri et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…También, al migrar abruptamente al método de compra online, los consumidores tienen en cuenta aspectos que pueden reducir al mínimo la intención de compra debido a esto surgen las reseña negativa en línea (Rifki & Pragita, 2019). Respecto a las reseñas del consumidor en los lugares de compras online, últimas investigaciones indican que las reseñas negativas y las reseñas de personas conocidas por el consumidor tienen un impacto en la intención de compra incluyendo a productos o marcas populares, por lo que las empresas las deben de tener muy en cuenta (Li & Liang, 2022).…”
Section: Antecedentes De La Investigaciónunclassified